ALGORITHMIC PREPARATION OF NAVIGATORS IN THE CONDITIONS OF INFORMATIVELY-COMMUNICATION PEDAGOGICAL ENVIRONMENT (Journal of Information Technologies in Education (ITE), 2010)
In the article the questions of algorithmic preparation of navigators are examined in the conditions of informative of communication pedagogical environment. For teaching of algorithmization and programming it is suggested to use the integrated environment of study of course of «Basis of algorithmization and programming» (http://weboap.ksu.ks.ua), which is developed in RIIT of the Kherson state university.
Keywords: algorithmic preparation; informatively-communication pedagogical environment; navigators